1988
DOI: 10.1007/bf00214380
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a major secretory protein from bull seminal vesicles to bovine spermatozoa

Abstract: The seminal vesicles synthesize in an androgen-dependent manner a neutral protein of 13.5 kDa molecular weight that makes up about 40% of their secretion ("major protein"). An antiserum against this protein raised in rabbits was used to localize the antigen within the seminal vesicles. In addition to intraluminal secretion of the seminal vesicles and the ampulla of the vas deferens, ejaculated and ampullary spermatozoa revealed an intense immunoreaction, which was restricted to the neck region of the sperm hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Bovine seminal plasma proteins bind to the surface of plasma membrane of spermatozoa (Aumuller et al, 1988), more specifically, to the mid piece of sperm once they pass the ampulla of the vas deferens during emission (Sanchez-Luengo et al, 2004). Indirect immunofluorescent labeling of fixed ejaculated sperm with anti-PDC-109 antiserum revealed labeling over the acrosomal region of the sperm head, which is the region known to bind to oviductal epithelium (Gwathmey et al, 2003).…”
Section: Binding Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine seminal plasma proteins bind to the surface of plasma membrane of spermatozoa (Aumuller et al, 1988), more specifically, to the mid piece of sperm once they pass the ampulla of the vas deferens during emission (Sanchez-Luengo et al, 2004). Indirect immunofluorescent labeling of fixed ejaculated sperm with anti-PDC-109 antiserum revealed labeling over the acrosomal region of the sperm head, which is the region known to bind to oviductal epithelium (Gwathmey et al, 2003).…”
Section: Binding Affinitymentioning
confidence: 99%
“…phosphatidylethanolamine, phosphatidylserine, phosphatidylinositol, phosphatic acid and cardiolipin (Desnoyers and Manjunath, 1992). In addition to their heparin-and lipid-binding activities, the BSP proteins interact with a variety of ligands including different collagens (type I, II, IV, V), fibrinogen, apolipoprotein A1, apolipoprotein A1/high-density lipoprotein complexes, (Aumuller et al, 1988), biding to choline phospholipids (Desnoyers and Manjunath, 1992), binding to mid piece of sperm and sperm motility (Sanchez-Luengo et al, 2004), oviductal sperm reservoir (Gwathmey et al, 2003), capacitation and AR (Therien et al, 1995) and cryoinjury (Therien et al, 1999). and calmodulin (Therien et al, 1995), in free form or associated with HDL (Manjunath et al, 1989).…”
Section: Binding Affinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this process remains to be elucidated, however. Thus, Aumtiller et al [20] have reported that Major Protein (PDC-109) binds to the midpiece of spermatozoa to a 65-67 kDa protein duplet and appears to initiate hyperactive sperm motility. On the other hand, Desnoyers and Manjunath [6] have shown that BSP-Al (PDC-109) binds specifically to phospholipids which contain the phosphorylcholine group, and proposed that this interaction may play a important role in the membrane modification that occurs during capacitation.…”
Section: Ligand-binding Capability and Quantitation Ofmentioning
confidence: 99%
“…For example, alterations in flagellar movements can be observed when soluble fac tors arc attached to or lost from the cells [2], Sperm-coating antigens restricted to the middie-piece domain have been suggested to in fluence the motility of golden hamster [52] and bovine [24] spermatozoa. In the rat.…”
Section: Discussionmentioning
confidence: 99%